2011
DOI: 10.1016/j.optcom.2011.03.016
|View full text |Cite
|
Sign up to set email alerts
|

NOON states in entangled cavities

Abstract: We show how NOON states may be generated entangling two cavities by passing atoms through them. The atoms interact with each cavity via two-photon resonant transitions. We take advantage of the fact that depending on the state the atom enter (excite or ground), it leaves or takes two photons per interaction and leaves the cavities in a pure state.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…We consider an ion in a two-dimensional Paul trap [10], and we assume that the ion is driven by a plane wave…”
Section: Ion Vibrating In Two Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider an ion in a two-dimensional Paul trap [10], and we assume that the ion is driven by a plane wave…”
Section: Ion Vibrating In Two Dimensionsmentioning
confidence: 99%
“…The greatest N for which N 00N states have been produced is N = 5 [4]. Most schemes to generate this class of states are either for optical [4,5] or microwave [10] fields.…”
Section: Introductionmentioning
confidence: 99%
“…that represents a superposition of N particles in mode a with zero particles in mode b and zero particles in mode a with N particles in mode b. Most schemes to produce NOON states are in the optical regime [13]; however, in the case of cavity fields, it has been shown that NOON states with N = 4 may be generated [17], while in ion-laser interactions [18] NOON states may be generated for larger N 's [19]. Such nonclassical states have also been generated in acoustic wave resonators with high fidelities [20].…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical and experimental schemes have been proposed for generating the NOON states via optical components [15,[20][21][22][23][24][25][26][27], cold atomic ensemble [28], superconducting circuits [29,30], and cavity quantum electrodynamics (QED) [31][32][33][34][35][36][37][38][39]. However, the success probabilities of the proposals based on the linear optical components are very low as the number of particles increasing [22].…”
mentioning
confidence: 99%